Parallel flow driven by electron cyclotron heating in the helically symmetric experiment. (1st June 2022) - Yamamoto, Y.; Murakami, S.; Chang, C.C.; Kumar, S.T.A.; Talmadge, J.N.; Likin, K.M.; Anderson, D.T.
Abstract: Spontaneous plasma flows have been observed in electron cyclotron heating (ECH) plasmas in the helically symmetric experiment. A smaller parallel flow was observed in the quasi-helically symmetric configuration compared with that observed in the Mirror configuration, although the mirror configuration has a larger neoclassical viscosity. Using the GNET code, we evaluate the electromagnetic and collisional forces induced by ECH. We also evaluate the parallel flow driven by the ECH force, by solving the momentum balance equations and Ampère law. The obtained flows show reasonable agreement with results obtained from experiments. This work indicates that the radial electron current generated by ECH could drive the parallel flow.